Inhibition of pyrimidine de novo synthesis fosters Treg cells and reduces diabetes development in models of Type 1 Diabetes - Hannah Hipp; Camilla Tondello; Hanna Gmehling; Lena K. Scholz; Antigoni Stavridou; Maike Becker; Anne-Marie Bührer; Edith Hintermann; Sandra M. Dirschl; Till M. Johannsmann; Martin G. Scherm; Hella Kohlhof; et al. (Molecular Metabolism)
Objective: In autoimmune Type 1 Diabetes (T1D), aberrant immune activation promotes regulatory T cell (Treg) impairments thereby boosting progression of islet autoimmunity. Consequently, there is a progressive destruction of the insulin-producing beta cells in the pancreas. Controlling overshooting immune activation represents a relevant approach to allow for efficient Treg-targeting by broadening the window of opportunity to induce Tregs. Methods: We investigated the effect of restricting pyrimidine de novo synthesis during islet autoimmunity and T1D by Dihydroorotate dehydrogenase (DHODH) inhibition using the next-generation DHODH inhibitor Vidofludimus calcium. We assessed Treg-inducing features of DHODH inhibition in T cells from ongoing murine islet autoimmunity and human T1D in vitro. To dissect the functional relevance of these observations, we tested the impact of DHODH inhibition on interfering with autoimmune activation and disease progression in pre-clinical models of T1D in vivo. Results: We show that DHODH inhibition results in enhanced Treg induction in vitro especially during increased immune activation and reduced T cell proliferation. In addition, Vidofludimus calcium reduced T1D incidence in two mouse models. On the cellular level, treated mice showed reduced T cell activation accompanied by increased Treg frequencies. Conclusions: We demonstrate that restricting pyrimidine de novo synthesis by next-generation DHODH inhibition is a strategy to interfere with autoimmune activation while fostering Tregs.